COVID-19 vaccines and vaccine administration. (25th March 2021) - Gordon, Charlotte; Porteous, Debbie; Unsworth, John
Abstract : This article provides an overview of current COVID-19 vaccines available within the UK, including their mode of action, storage and handling. It outlines the recommendations on priority groups for vaccination and provides insight into the training recommendations for vaccinators.